2010
DOI: 10.1038/labinvest.2010.125
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of islets by nuclei counting and light microscopic analysis

Abstract: Islet enumeration in impure preparations by conventional dithizone staining and visual counting is inaccurate and operator dependent. We examined nuclei counting for measuring the total number of cells in islet preparations, and we combined it with morphological analysis by light microscopy (LM) for estimating the volume fraction of islets in impure preparations. Cells and islets were disrupted with lysis solution and shear, and accuracy of counting successively diluted nuclei suspensions was verified with: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
5
19
0
Order By: Relevance
“…2 and Table 4) and were comparable to expected values, 16,18 thereby verifying the quantitative reliability of both nuclei counting and DNA measurement with tissue encapsulated in alginate. Data suggested that 10% (w/v) Triton X-100 in the lysis buffer resulted in effective liberation of nuclei from cells in barium alginate.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…2 and Table 4) and were comparable to expected values, 16,18 thereby verifying the quantitative reliability of both nuclei counting and DNA measurement with tissue encapsulated in alginate. Data suggested that 10% (w/v) Triton X-100 in the lysis buffer resulted in effective liberation of nuclei from cells in barium alginate.…”
Section: Discussionsupporting
confidence: 82%
“…15,16 Examination of viability by assessment of membrane integrity with vital stains such as fluorescein diacetate/propidium iodide does not reflect true viability because it may not account for cells undergoing early cell death processes, during which cells have not yet developed damage to their cell membrane. 8,9,17,18 Measures of cellular energetic state, including ATP content [19][20][21][22][23][24] and ATP/ADP and related ratios, [25][26][27] have been investigated with modest success.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these techniques turn out to perform poorly in predicting the transplantation success, because the content of the mentioned substances varies from donor to donor. Pisania et al, 11 2010, evaluated the number of islet nuclei taking advantage of their homogeneity. Other methods are based on estimation of the amount of tissue from the extracted DNA (Stegenmann et al, 1998) or the total protein contents.…”
Section: State-of-the-artmentioning
confidence: 99%